Smart distribution board overload detector by using microcontroller - Mohammad Azmi, Nurfiza Atikah; Mohd Jamail, Nor Akmal; Othman, Nordiana Azlin; Ismail, Muhammad Nafis; Kamarudin, Qamarul Ezani (Penerbit UTHM, 2020)
A statistic by Economic Planning Unit (EPU) on the electricity growth in Malaysia has shown an increment in line with economic growth [1]. In line with government policies, the energy supply industry has been molding itself to cater to the rapid development of the nation in hopes of creating a better and smarter nation [2]. There are many developments and implementation of smart energy consumption to save energy and cater to future energy challenges.